2019
DOI: 10.1002/jcp.28771
|View full text |Cite
|
Sign up to set email alerts
|

miR‐324‐5p protects against oxidative stress‐induced endothelial progenitor cell injury by targeting Mtfr1

Abstract: Endothelial progenitor cells (EPCs) belong to bone marrow-derived myeloid progenitor cells that have strong proliferative ability. Dysregulation of miRNAs after acute myocardial infarction (AMI) can result in EPCs injury, thus we hypothesize that correction of miRNA expression may contribute to the tolerance of EPCs against oxidative stress. The peripheral blood of healthy volunteers and patients with ST-segment elevation myocardial infarction (STEMI) was clinically collected. EPCs derived from peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Mtfr1, as a mitochondrial protein, contains a short polyformaldehyde‐rich region . The function of Mtfr1 is mainly related to the mitochondrial inner membrane . Recent findings indicate that Mtfr1 has a close relationship with apoptosis and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mtfr1, as a mitochondrial protein, contains a short polyformaldehyde‐rich region . The function of Mtfr1 is mainly related to the mitochondrial inner membrane . Recent findings indicate that Mtfr1 has a close relationship with apoptosis and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…26 The function of Mtfr1 is mainly related to the mitochondrial inner membrane. 26,27 Recent findings indicate that Mtfr1 has a close relationship with apoptosis and oxidative stress. 15 In the present study, we demonstrated that overexpression of Mtfr1 could partially block the role of Gpr19 inhibition in suppressing oxidative stress and apoptosis in NRCMs induced by OGD/R.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers found that miRNAs can bind to 3’ untranslated region (3’ UTR) of target messenger RNAs (mRNAs) and negatively regulate gene expression by transcriptional or translational inhibition [ 1 , 2 , 3 ]. MiR-574-5p are implicated in the pathophysiology of many tumors, including breast cancer, colorectal cancer and other oncoma [ 4 , 5 , 6 ]. In addition, miR-574-5p is a very important regulator for cell migration and proliferation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…MTFR1, a target gene of miR-324-5p ( Ye et al, 2019 ), encodes a mitochondrial protein that can promote mitochondrial fission and is crucially involved in oxidative stress. Suppressing MTFR1 translation attenuates mitochondrial fission, apoptosis and myocardial infarction ( Wang et al, 2015 ), which indicates that excessive expression of MTFR1 aggravates mitochondrial fission and apoptosis, meanwhile regulating MTFR1might afford protection against oxidative stress-induced endothelial progenitor cell injury ( Chen et al, 2019 ). Mitochondrial function has a profound effect on DR ( Shao et al, 2019 ), among these influences, MTFR1 in all probability might play a vital role in the mechanism of DR. ACADL belongs to the mitochondrial flavoenzyme family that are commonly involved in fatty acid.…”
Section: Discussionmentioning
confidence: 99%